CHARACTER BUILDING IN UNIVERSITY STUDENTS: COMPREHENSION OF ISLAMIC VALUE & DISCIPLINE - M. Kurniawan; Juliandri Hasnur; Syafni Yelvi Siska (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
The research aimed to assess the effects of students’ understanding of Islamic values, the impact of discipline, and their simultaneous influence on character building. A quantitative ex post facto design was employed, using multiple linear regression analysis via SPSS. The study was conducted at Politeknik Pelayaran Sumatera Barat (Poltekpel Sumbar), studies over a three‑month period from May to August 2025. The population comprised 168 students from batch VIII and IX, of whom 50 batch VIII students participated in the pilot test and 118 batch IX students served as the research sample through total sampling. The instrument was a questionnaire that had undergone validity and reliability testing and was administered directly to respondents outside scheduled class hours. The results indicated that Islamic values had significant effect on students’ character building (t=7.101 > t=1.66), so hypotheis 1 was accepted. Then, discipline exerted significant effect on students’ character building (t=3.442 > t=1.66), in other words, hypothesis 2 was accepted. Furthermore, islamic values and discipline have simultaneous effect on students’ character building (F=115.253 > F=3.07), it means hypothesis 3 was accepted. Based on these findings, it is recommended that Poltekpel Sumbar integrates modules reinforcing Islamic values and discipline training into the curriculum, alongside implementing a dedicated mentoring and discipline‑monitoring system. Embedding structured modules on Islamic values and discipline within the curriculum can serve as an effective strategy for fostering students’ character development, thereby informing institutional policy and pedagogical practices.